2020
DOI: 10.1016/j.jamda.2020.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exergaming on Cognitive and Social Functioning of People with Dementia: A Randomized Controlled Trial

Abstract: Objectives: Physical activity in people with dementia (PwD) may enhance physical and mental functioning. Exergaming, which combines physical exercise with cognitive stimulation in a gaming environment, was developed to overcome barriers in performing physical activities. We evaluated the effects of exergaming in day care centers (DCCs) for PwD and informal caregivers (ICs). Design: A randomized controlled trial among 23 DCCs across the Netherlands randomized to exergaming (interactive cycling during 6 months) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 47 publications
0
44
0
2
Order By: Relevance
“…people with mild MNCD [25,71]. A possible reason for the difference with previous bicycle training research is that our participants performed standing balance exergames that required participants to stand and perform stepping movements, which directly addresses gait and balance [72].…”
Section: Discussionmentioning
confidence: 97%
“…people with mild MNCD [25,71]. A possible reason for the difference with previous bicycle training research is that our participants performed standing balance exergames that required participants to stand and perform stepping movements, which directly addresses gait and balance [72].…”
Section: Discussionmentioning
confidence: 97%
“…Of these, 2 studies did not find any adverse events of the interventions during the study period [ 37 , 38 ]. The 3 remaining studies spotted some adverse events, but they were comparable between groups [ 34 - 36 ]. Specifically, Fiatarone Singh et al [ 35 ] found 6 adverse events distributed as follows: 3 events in the serious game plus conventional exercises group, 1 event in the conventional exercises group, 0 events in the serious game group, and 2 events in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…The adverse events reported in this study were falls during assessment (n=3) and exacerbations of pre-existing arthritis symptoms (n=3). In the second study [ 36 ], the mean number of falls was not statistically different between the exergame group and control group after the intervention (1.2 vs 2.0) and after a 6-month follow-up (1.5 vs 1.5). The last study reported that there was 1 adverse event during the study period, which occurred in a participant from the serious game group [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…у вигляді однієї статті на рік та з 2009-2014 рр.− 10-20 статей на рік, що пов'язано з виходом серії Wii Fit від Nintendo, яка стала новим словом в медичній реабілітології та геріатрії. Зокрема в дослідженнях [6,7], базу для яких закладено в даний період, розкрито результати застосування Wii Fit and Було встановлено поліпшення когнітивних функцій при реабілітації осіб с деменцією [8] та прискорення реакції в тесті ІС на дистрес [9]. Хоча дані дослідження і дали певні позитивні результати, доцільно вважати, що для кращого відображення стійкості до стресу та тренованості параметри, пов'язані з вираженістю стресу, необхідно виражати через показник відновлення RMSSD.…”
unclassified
“…Загалом з 701 публікації за запитом exergames, в базі даних Science Direct, 12300 публікацій в Google Academia, понад 100 видань в базі Researcher Gate та 144 статей в базі WоS, більша частина дослідних робіт вийшла у світ протягом 2015-2020 рр. і належить до трьох наукових напрямів: реабілітологія [6][7][8][9][10][11], геронтологія і геріатрія [12][13][14][15][16] та педагогіка [1,[17][18][19][20][21][22]. Найбільш ранні з них присвячено впливу ексергеймінгу на боротьбу з дитячим ожирінням [17], а також першим результатам використання танцювальних відеоігор в педагогіці [18].…”
unclassified